2018
DOI: 10.1016/j.celrep.2018.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative CRF and α1 Adrenergic Signaling in the VTA Promotes NMDA Plasticity and Drives Social Stress Enhancement of Cocaine Conditioning

Abstract: SUMMARYStressful events rapidly trigger activity-dependent synaptic plasticity, driving the formation of aversive memories. However, it remains unclear how stressful experience affects plasticity mechanisms to regulate appetitive learning, such as intake of addictive drugs. Using rats, we show that corticotropin-releasing factor (CRF) and α1 adrenergic receptor (α1AR) signaling enhance the plasticity of NMDA-receptor-mediated glutamatergic transmission in ventral tegmental area (VTA) dopamine (DA) neurons thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 84 publications
(115 reference statements)
1
26
3
Order By: Relevance
“…Brief exposure to acute social defeat stress enhances the conditioned effects of psychostimulants, which may in turn promote the acquisition of self-administration behavior. Compared to non-defeated control animals, both mice and rats that are socially defeated immediately before receiving an injection of cocaine subsequently develop a greater preference for the drug-paired environment during conditioned place preference (CPP) testing ( McLaughlin et al, 2006 ; Montagud-Romero et al, 2015 ; Tovar-Diaz et al, 2018 ). Likewise, exposure to social defeat stress over five consecutive days can double the rate of cocaine self-administration acquisition ( Fig.…”
Section: Animal Models Of Social Stress and Pathological Patterns Of mentioning
confidence: 99%
“…Brief exposure to acute social defeat stress enhances the conditioned effects of psychostimulants, which may in turn promote the acquisition of self-administration behavior. Compared to non-defeated control animals, both mice and rats that are socially defeated immediately before receiving an injection of cocaine subsequently develop a greater preference for the drug-paired environment during conditioned place preference (CPP) testing ( McLaughlin et al, 2006 ; Montagud-Romero et al, 2015 ; Tovar-Diaz et al, 2018 ). Likewise, exposure to social defeat stress over five consecutive days can double the rate of cocaine self-administration acquisition ( Fig.…”
Section: Animal Models Of Social Stress and Pathological Patterns Of mentioning
confidence: 99%
“…), or conversely, by synergizing with corticotrophin‐releasing factor to enhance NMDA‐dependent and IP 3 ‐ and calcium‐mediated plasticity (Tovar‐Díaz et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The VTA itself is a target for regulation via other systems. This involves glutamate acting via NMDA and a-amino-3hydroxy-5-methylisoxazole-4-propionate receptors, GABAergic interneurons, and inputs that constrain the activity of the VTA, as well as a plethora of modulatory signals including acetylcholine, stress-related signaling encompassing both corticoids and corticoid releasing factor, and finally, noradrenaline (Guiard et al 2008;Lester et al 2008Lester et al , 2010Parker et al 2010;Morikawa and Paladini 2011;Polter and Kauer 2014;Schmidt and Weinshenker 2014;Tovar-D ıaz et al 2018).…”
mentioning
confidence: 99%
“…In adverse circumstances, it is adaptive to rapidly and effectively learn which stimuli predict beneficial outcomes. Prior rodent studies have shown that stress enhances the learned preference for a cocaine-associated context 13,14 , though it was unclear if acute stress similarly facilitated learning driven by natural rewards. Here, we addressed this question by utilizing a Pavlovian task in which an auditory CS signaled the upcoming delivery of a food reward.…”
Section: Discussionmentioning
confidence: 99%